Finance and development - International Monetary Fund (Washington, D.C International Monetary Fund (IMF), 2002)
A quarterly magazine published by the IMF, presents articles and book reviews on a wide variety of topics in international economics and finance, as well as economic development.
Finance & development is published quarterly in English, Arabic, Chinese, French, Russian, and Spanish. English edition. The library has the Eng. language ed. only. An Arabic copy is also available at library: Vol 45 (2008), 47 (2010) and 48 (2011) are not available at the library
Keywords: Financial economics; DEVELOPMENT FINANCE; ECONOMIC DEVELOPMENT; FINANCE; PERIODICALS